The child with speech disorders: clinical aspects and ethical reflections - Errante, Antonio (Medicina e Morale, 2024)
In children, language is an evolutionary process. This is of decisive importance for any attempt at interpreting disorders and defining diagnostics A slight deficit detected early on may indeed be mild, but it may also herald profound disturbances whose consequences will reveal themselves over time. Typically, the first warning sign is a real delay in the onset of organised speech, in the absence of noticeable sensory impairments such as deafness.